Humor and theory of mind in children under five years old (2018)
This book intends to show the results of the research into the emergence of teasing actions in children between 11-40 months old. This study was based on the methodology of parents as informants with a naturalistic, longitudinal observation design. Eleven mothers with children between 11-40 months old observed and recorded the teasing actions that their children performed in everyday life. The results showed how these actions emerge differentially in each child but, at the same time, demonstrated the existence of trajectories with common components. Four trajectories, five teasing categories, one humor category based on tomfoolery, and seven game subcategories were classified from the observations and records sent by the mothers. The results also aim to validate the existence of two main teasing types that arise from the analysis of shared intentions. Similarly, this study contributed elements that question some rigid positions that defend the development of theory of mind (ToM) in children at the age of four. In analyzing the cognitive demands of teasing actions, an important development in understanding other minds in children between 11-40 months old was determined. It was established that there are cognitive demands in both the production and appreciation of forms of teasing that suggest a developed understanding of one’s own mental states and those of others which, until now, had been considered an ability associated with language development and age (from four years old)